Analysis of the situation of domestic game damage and forage ground management - Antal, Borbála; Rédei, Károly; Csajbók, József (Acta Agraria Debreceniensis, 2014)
Game damage is an important problem in home wildlife management, because game managers pay more and more money for game damage year by year. Crop fields can do an appreciable part in reduction of game damages. The aim of the research is to survey the situation of domestic game damage and wildlife forage ground management. (Which are the most used plants on crop fields, how current are the using of seed mixtures, which are the most typical game damages, as well as which are the most applied game control methods?)It can be stated that the number of plant species sown on crop fields is quite low. Mostly corn and alfalfa are raised, though besides those many other plants are suitable to grow on crop fields. Rising value of game damage and big proportion of the agricultural game damage are well traceable from the questionnaires, too.